2018
DOI: 10.1098/rspb.2017.2577
|View full text |Cite
|
Sign up to set email alerts
|

Restoration and repair of Earth's damaged ecosystems

Abstract: Given that few ecosystems on the Earth have been unaffected by humans, restoring them holds great promise for stemming the biodiversity crisis and ensuring ecosystem services are provided to humanity. Nonetheless, few studies have documented the recovery of ecosystems globally or the rates at which ecosystems recover. Even fewer have addressed the added benefit of actively restoring ecosystems versus allowing them to recover without human intervention following the cessation of a disturbance. Our meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
260
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(280 citation statements)
references
References 45 publications
(82 reference statements)
12
260
1
7
Order By: Relevance
“…Our results are consistent with other studies showing that, where possible, regrowth offers cost‐effective opportunities to deliver conservation and carbon benefits in agricultural regions (Crouzeilles et al ; Meli et al ; Jones et al ). Where active reforestation is required, we suggest that recruitment and recruit survival is a high priority.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with other studies showing that, where possible, regrowth offers cost‐effective opportunities to deliver conservation and carbon benefits in agricultural regions (Crouzeilles et al ; Meli et al ; Jones et al ). Where active reforestation is required, we suggest that recruitment and recruit survival is a high priority.…”
Section: Discussionsupporting
confidence: 93%
“…This confirms findings by Rey Benayas et al (2009), Moreno-Mateos et al (2017), and Jones et al (2018), who also reported incomplete recovery of restored ecosystems worldwide, highlighting that conservation of intact ecosystem has highest priority. This confirms findings by Rey Benayas et al (2009), Moreno-Mateos et al (2017), and Jones et al (2018), who also reported incomplete recovery of restored ecosystems worldwide, highlighting that conservation of intact ecosystem has highest priority.…”
Section: Discussionsupporting
confidence: 89%
“…Recent research has pointed out a number of cases in which natural regeneration and recovery following disturbance can be more successful than active restoration, such as planting (Crouzeilles et al, 2017;Jones et al, 2018). Recent research has pointed out a number of cases in which natural regeneration and recovery following disturbance can be more successful than active restoration, such as planting (Crouzeilles et al, 2017;Jones et al, 2018).…”
Section: Discussionmentioning
confidence: 99%